Responses to species-specific vocalizations in the auditory cortex of awake and anesthetized guinea pigs - Syka, Josef; Suta, Daniel; Popelár, Jirí (Hearing research, 2005)
Species-specific vocalizations represent an important acoustical signal that must be decoded in the auditory system of the listener. We were interested in examining to what extent anesthesia may change the process of signal decoding in neurons of the auditory cortex in the guinea pig. With this aim, the multiple-unit activity, either spontaneous or acoustically evoked, was recorded in the auditory cortex of guinea pigs, at first in the awake state and then after the injection of anesthetics (33 mg/kg ketamine with 6.6 mg/kg xylazine). Acoustical stimuli, presented in free-field conditions, consisted of four typical guinea pig calls (purr, chutter, chirp and whistle), a time-reversed version of the whistle and a broad-band noise burst. The administration of anesthesia typically resulted in a decrease in the level of spontaneous activity and in changes in the strength of the neuronal response to acoustical stimuli. The effect of anesthesia was mostly, but not exclusively, suppressive. Diversity in the effects of anesthesia led in some recordings to an enhanced response to one call accompanied by a suppressed response to another call. The temporal pattern of the response to vocalizations was changed in some cases under anesthesia, which may indicate a change in the synaptic input of the recorded neurons. In summary, our results suggest that anesthesia must be considered as an important factor when investigating the processing of complex sounds such as species-specific vocalizations in the auditory cortex.
Keywords: Acoustic Stimulation; sluchové evokované potenciály; Species Specificity; akustická stimulace; sluchové korové centrum; Auditory Perception; Animals; morčata; Guinea Pigs; regresní analýza; zvířata; Auditory Cortex; sluchová percepce; mužské pohlaví; Male; Regression Analysis; vokalizace zvířat; zvuková spektrografie; Vocalization, Animal; Evoked Potentials, Auditory; Sound Spectrography; druhová specificita